Strategies for Improving Consumer Utilization of Labels on Processed Food Products in Aba Metropolis, Abia State - A. , Durueke; A.I, Asouzu (Journal of Home Economics Research, 2024)
This study focused on strategies for improving consumer utilization of labels on processed foods in Aba Metropolis, Abia State. Specifically, it determined strategies to be adopted by: consumers themselves; manufacturers; and distributors/traders. The study utilized descriptive survey research design. Population was made up of three groups: consumers, manufacturers and distributors processed foods products in the area of study. A multistage technique was used to select a sample of 260 respondents (comprising 120 consumers, 45 manufacturers, 95 distributors) who participated in the study. Questionnaire was used for data collection. Mean and standard deviation were used to analyse data. Findings include: eight each of consumers-related strategies with mean (X) scores of 2.61-3.14; manufactures related strategies with mean (X) scores 2.87-3.17; and distributors related strategies with mean (X) scores of 3.02-3.15. These strategies which could be adopted by consumers, manufactures and distributors, include, among others, consumers to form the habit of reading labels processed foods, manufactures to include manufacturing date on processed foods, and distributors are to display the price tag on the processed foods. Five recommendations were made. These include that regulatory authorities (like NAFDAC) should monitor and ensure that manufacturers fulfil their responsibilities of raising consumers’ awareness on the utilization of information on food labels such as ingredients, manufacture/expiration date, NAFDAC and Batch numbers.